Training on Processing Used Cooking Waste into Solid Soap and Liquid Soap at the Karang Taruna of Palur Village. - Wardani, Tatiana siska; Suhatmi, Erna Chotidjah; Artini, Kusumaningtyas Siwi; Dewi, Belinda Arbitya; Erikania, Susanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Karang Taruna Saras Muda Palur Village in creating a clean environment, one of which is collecting used cooking oil so that it does not pollute the environment and can have a bad impact on health. One of the uses of used cooking oil that can be turned into a product that has a selling value is soap. The purpose of this PKM is to increase understanding and training in liquid soap and solid soap that can be sold to increase the income of Karang Taruna Saras Muda Palur Village. The methods used are socialization, soap making training and entrepreneurship training. This PKM produces a processed product from used cooking oil waste and increases partner understanding after the pretest and posttest. From the activities above, it can be concluded that the results of the PKM related to the utilization of used cooking oil waste carried out by Karang Taruna Saras Muda Palur Mojolaban Sukoharjo have been carried out well and smoothly.